2021
DOI: 10.6065/apem.2040208.104
|View full text |Cite
|
Sign up to set email alerts
|

Single random measurement of urinary gonadotropin concentration for screening and monitoring girls with central precocious puberty

Abstract: Single random measurement of urinary gonadotropin concentration for screening and monitoring of girls with central precocious pubertyRunning title: Urinary gonadotropin in central precocious puberty

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…In contrast, the FSH peak after GnRH test did not correlate with any of u 24 FSH or u 24 LH. A recent study showed very similar results on randomly collected urinary samples ( Lee et al , 2021 ). Moreover, the correlation coefficients found herein were much more comparable with previous data ( Demir et al , 2016 ; Lucaccioni et al , 2016 ; Kolby et al , 2017 ), and higher than some others ( Lee et al , 2021 ; Zhan et al , 2021 ).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In contrast, the FSH peak after GnRH test did not correlate with any of u 24 FSH or u 24 LH. A recent study showed very similar results on randomly collected urinary samples ( Lee et al , 2021 ). Moreover, the correlation coefficients found herein were much more comparable with previous data ( Demir et al , 2016 ; Lucaccioni et al , 2016 ; Kolby et al , 2017 ), and higher than some others ( Lee et al , 2021 ; Zhan et al , 2021 ).…”
Section: Discussionsupporting
confidence: 61%
“…Several studies have proposed various protocols based on simple emptying of the bladder before bedtime and collecting in the morning, accurate notification of the time between the last emptying and collection, or standardization of the hour of collection, at one or several times ( Kolby et al , 2017 ; Shim et al , 2019 ; Lee et al , 2021 ; Demir et al , 2023 ). Currently, no study has compared these methods in order to show a potential superiority.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, there were significant differences in SHBG, leptin, and APN levels among the normal group, overweight group, and obese group, suggesting that obesity has a certain influence on the levels of SHBG, leptin, and APN and has a certain relationship with precocious puberty. The authors believe that the main reason is that the secretion of estrogen and androgen in girls with CPP increases significantly, and the accumulation of fat will cause compensatory hyperinsulinemia in girls, reduce the synthesis of SHBG, and affect the secretion of APN; at the same time, exogenous adipokine changes the release of GnRH pulse in the hypothalamus by binding with the leptin receptor, leading to the increase in LH and FSH levels [ 28 , 29 ]. Therefore, obesity-induced changes in GnRH test results in girls with CPP may be related to the changes in SHBG, leptin, and APN levels, which suggests that the effect of BMI on the gonadal axis should be considered when interpreting GnRH test results.…”
Section: Discussionmentioning
confidence: 99%
“…CPP not only leads to physical and psychological challenges for affected children and their families but also necessitates early diagnosis and appropriate management to mitigate potential long-term health consequences ( 2 ). Although tools for CPP diagnosis have been established ( 3 , 4 ), continuous research is being conducted on new markers to improve diagnosis and monitoring ( 5 7 ). Understanding the causes and progression of CPP can aid the development of enhanced diagnostic tools and contribute to the advancement of improved treatment options.…”
Section: Introductionmentioning
confidence: 99%